The “Punto Organico”: an Italian history (RT. A Journal on Research Policy and Evaluation, 2015)
The  Recruitment  of  professors  and  researchers  by  Italian  public  Universities  is  limited not  only  by  the  financial  constraints  imposed  by  National  laws,  but  also  by  the  conversion  of  the financial resources into positions according to a rule established a few years ago by the Ministry of Education and expressed by the so-called  “Punto Organico” (P.O.).The  origin  of  the  notion  of  P.O.  is  traced  back  to some  statistical  studies  performed  more  than  a decade  ago  .  Its  subsequent  application  to  university  recruiting  follows  from    a  sequel  of administrative actions taken by the Ministry but it is not based on an explicit (and formally required) legal formulation. The  recent  structural  evolution  of  the  university  system  and  some  changes  in  the  legislation  have further  weakened  the  justification  for  such  a  constraint.    An  alternative  (and  legally  consistent) mechanism for keeping under control the projected expenses  for personnel is proposed